A method for preparing high-strength SiO2 aerogel with adjustable deformation ability

By using polyhedral oligosilsesquioxane and binary or polyorganic acids, high-strength SiO2 aerogel with adjustable deformation ability was prepared, which solved the problem of insufficient mechanical properties of SiO2 aerogel, and achieved strength improvement and deformation A combination of capability adjustment and multifunctional performance.

CN117185303BActive Publication Date: 2025-02-07UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310985422.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-07
Estimated Expiration
2043-08-07

AI Technical Summary

Technical Problem

The mechanical properties of SiO2 aerogels have problems such as low strength, high brittleness and poor processing performance, which leads to insufficient stability and performance when used in actual environments.

Method used

A high-strength SiO2 aerogel with different deformation abilities is prepared using polyhedral oligosilsesquioxane as raw material and binary or polyorganic acids of different structures as connection components. The method includes mixing cage polysilsesquioxane with organic reagent, adding organic acid solution, and after dropwise addition, aging, solvent replacement and drying, the high-strength SiO2 aerogel is finally obtained.

Benefits of technology

The comprehensive improvement of the mechanical properties of SiO2 aerogel was achieved, with the strength increased to 5.36~26.9MPa, and the fracture strain rate was 38.7~86.7%. At the same time, the low thermal conductivity and superhydrophobic properties were maintained, ensuring its stability in practical applications. and versatility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185303B_ABST
    Figure CN117185303B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of aerogel material preparation, and provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation capacity, so as to solve the problems of low strength, high brittleness and poor processability of SiO2 aerogel. The present invention first prepares a cross-linking reagent composed of an organic acid, an organic reagent and deionized water, and drips it dropwise into an organic solvent containing an octaamino cage-type polysiloxane to induce a gelation reaction, and then after gelation, the high-strength SiO2 aerogel with adjustable deformation capacity is obtained by aging, solvent replacement and normal pressure drying. The present invention realizes the comprehensive improvement of the mechanical properties of SiO2 aerogel, which not only solves the disadvantages of low strength and high brittleness, but also the deformation capacity can be flexibly adjusted according to different organic acids, fundamentally overcoming the problem of poor mechanical properties of SiO2 aerogel; at the same time, it ensures that the aerogel has both thermal insulation performance and hydrophobic performance; in addition, the present invention completes the gelation reaction in one step, greatly simplifying the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel material preparation, relates to the preparation technology of SiO2 aerogel, and specifically provides a method for preparing high-strength SiO2 aerogel with adjustable deformation ability. Background Art

[0002] As a multifunctional material, SiO2 aerogel has structural characteristics such as high specific surface area, low density, high porosity and mesoporous interconnected nano-skeleton, so it is highly expected in the fields of thermal insulation, catalysis, adsorption, optics and energy. At present, thermal insulation has become the key application direction of SiO2 aerogel. The three-dimensional interconnected nanoporous skeleton formed in the sol-gel process has a sufficient number of path ends to prevent solid heat transfer. The mesoporous size can inhibit the convection collision of air molecules, effectively blocking solid-phase heat conduction and gas-phase heat convection. The resulting thermal conductivity is comparable to or even lower than that of air; however, the structural characteristics of high porosity and the point-to-point rigid connection mode between gel particles lead to a series of mechanical performance disadvantages, such as low strength, high brittleness, poor processing performance, etc., which makes SiO2 aerogel unable to be used alone in actual environments.

[0003] At present, various commercial products related to SiO2 aerogel emerge in an endless stream. Although they have formed an absolute advantage over traditional thermal insulation materials in terms of performance, most of these products are made of powdered SiO2 aerogel compounded with other materials, which destroys the structural integrity and continuity of SiO2 aerogel and greatly reduces the performance advantage of SiO2 aerogel. In order to overcome this problem, researchers have actively tackled the structural design and performance improvement of high-strength SiO2 aerogel, forming effective means such as the introduction of elastic groups, polymer and nanofiber composite reinforcement. The introduction of elastic groups refers to the use of organic siloxanes containing elastic functional groups as precursors, which can not only adjust the pore structure during the gelation process, but also give the gel skeleton repulsion, so that the strength of the resulting SiO2 aerogel is improved and has a certain deformability. However, the improvement effect of this method is very limited and cannot fundamentally improve the mechanical properties, as described in the literature "X.Yue, J.Chen, H.Li, et al., One pot rapid synthesis of ultra high strength hydrophobic bulksilica aerogels, Mater.Chem.Front., 2020, 4, 2418-2427". Polymer and fiber composite reinforcement refers to the introduction of various polymers or fibers into the gel process to form a secondary skeleton structure, and using their structural and performance advantages to make the resulting SiO2 aerogel have higher strength and stronger deformation ability; in the research following this idea, the composite of SiO2 aerogel and polymer or fiber is mainly physical connection, which makes the composite aerogel structure have poor continuity and is in a structurally unstable state, and cannot be used stably for a long time in the actual environment, such as the literature "G. Zhang, A. Dass, A.-MM Rawashdeh, et al., Isocyanate-crosslinked silica aerogel monoliths: preparation and characterization, J. Non-Cryst. Solids, 2004, 350, 152-164", and "J. Ma, F. Ye, C. Yang, et al., Heat-resistant, strong alumina-modified silica aerogel fabricated by impregnating silicon oxycarbide aerogel with boehmite sol,Mater.Design,2017,131,226-231".

[0004] In order to comprehensively improve the mechanical property limitations of SiO2 aerogel, the present invention provides a method for preparing high-strength SiO2 aerogel with adjustable deformation capacity, thereby achieving comprehensive improvement of the mechanical properties of SiO2 aerogel. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing high-strength SiO2 aerogel with adjustable deformation ability, so as to solve the problems of low strength, high brittleness and poor processability of conventional SiO2 aerogel. The present invention proposes a new optimization strategy, using the new generation of "polyhedral oligomeric silsesquioxane" developed by the "Technical Progress Committee of the US Air Force Research Laboratory" in the 1990s as raw materials, and using binary or polybasic organic acids of different structures as connecting components, a series of SiO2 aerogels with different deformation abilities and high strength functions are successfully prepared, achieving a comprehensive improvement in the mechanical properties of SiO2 aerogels; at the same time, it is ensured that the obtained high-strength SiO2 aerogel has both thermal insulation properties and hydrophobic properties, ensuring that it has a development prospect of multifunctional applications.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a high-strength SiO2 aerogel with adjustable deformation capacity, characterized by comprising the following steps:

[0008] Step 1: Add cage-type polysilsesquioxane to the organic reagent and stir until completely dissolved;

[0009] Step 2: dissolving the organic acid into a mixed solvent of an organic reagent and deionized water, wherein the type and amount of the organic reagent are the same as those in step 1;

[0010] Step 3: at a preset reaction temperature, dropwise add the solution obtained in step 2 into the solution obtained in step 1 under continuous stirring, stop stirring when the addition is complete, and let stand to wait for gelation;

[0011] Step 4: performing aging and solvent replacement operations on the wet gel obtained in step 3;

[0012] Step 5: The alcohol gel obtained in step 4 is dried at normal pressure using a gradient temperature rise method to obtain a high-strength SiO2 aerogel with adjustable deformation capacity.

[0013] Preferably, in step 1, the cage-type polysilsesquioxane is octaaminophenyl cage-type polysilsesquioxane, and the usage ratio of the cage-type polysilsesquioxane to the organic reagent is 1 g:4-8 ml.

[0014] Preferably, in step 1, the organic reagent is tetrahydrofuran, acetone, ethanol, chloroform or acetonitrile.

[0015] Preferably, in step 2, the organic acid is a dibasic or polybasic organic acid, which is adaptively selected according to needs, and is preferably phthalic acid, 4,4'-biphenyldicarboxylic acid, malonic acid, sebacic acid, dimethyl terphenyl dicarboxylic acid, 1,3,5-benzenetricarboxylic acid, dodecanedioic acid, 2,6-naphthalene dicarboxylic acid, azobenzene-4,4-dicarboxylic acid or 1,1-cyclopropyl dicarboxylic acid.

[0016] Preferably, in step 2, the volume ratio of the organic reagent to deionized water is 1:0.2-0.5.

[0017] Preferably, the molar ratio of the caged polysilsesquioxane in step 1 to the organic acid in step 2 is 1:10-24.

[0018] Preferably, in step 3, the reaction temperature is 70-90° C., and the droplet acceleration rate is 0.1-0.4 ml / min.

[0019] Preferably, in step 4, the aging temperature is 60-80° C., and the aging time is 64-96 h.

[0020] Based on the above technical solution, the beneficial effects of the present invention are:

[0021] The present invention makes full use of the lightweight and high-strength structural characteristics and performance advantages of cage-type polysilsesquioxane, and successfully prepares a series of high-strength SiO2 aerogels with different deformation capabilities by constructing the connection relationship between the Si-O-Si hexahedral angles with binary or polybasic acids. The deformation capability is determined by the structural form of the binary or polybasic acid. The longer the straight chain, the stronger the deformation capability of the obtained SiO2 aerogel, and vice versa. The obtained SiO2 aerogel has a density of 0.13-0.29 g / cm 3 On the basis of the structure with low density and high porosity of 86.0-92.1%, the compressive strength is 5.36-26.9MPa and the fracture strain is 38.7-86.7%, which not only solves the disadvantages of low strength and high brittleness, but also the deformation capacity can be flexibly adjusted according to the different organic acids, fundamentally overcoming the problem of poor mechanical properties of conventional SiO2 aerogels. In addition, the obtained SiO2 aerogel has a significant nanoporous network morphology, which can effectively inhibit the conduction of gas phase heat convection and show a low thermal conductivity comparable to that of air, which is 0.02679-0.03360W / (m·K). Moreover, these SiO2 aerogels contain a large number of hydrophobic groups, which can show the hydrophobic characteristics of superhydrophobic materials without any modification, and the hydrophobic angle is as high as 147.3-158.6°, which avoids the damage of water vapor to the aerogel structure in the actual use environment and ensures the stability of long-term application.

[0022] In summary, the present invention provides a method for preparing high-strength SiO2 aerogel with adjustable deformation ability. First, a cross-linking reagent composed of an organic acid, an organic reagent and deionized water is prepared, and the cross-linking reagent is dripped dropwise into an organic solvent containing octaamino cage-type polysiloxane to induce a gelation reaction. Then, after gelation, the high-strength SiO2 aerogel with adjustable deformation ability is obtained through aging, solvent replacement and normal pressure drying. The method utilizes the reaction principle of condensation reaction of organic carboxylic acid groups and amino groups to form stable peptide bonds. The gelation reaction can be completed in only one step, which greatly simplifies the preparation process and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the SEM image of the high-strength SiO2 aerogel prepared in Example 1.

[0024] Figure 2 This is the SEM image of the high-strength SiO2 aerogel prepared in Example 2.

[0025] Figure 3 This is the SEM image of the high-strength SiO2 aerogel prepared in Example 3.

[0026] Figure 4 This is the SEM image of the high-strength SiO2 aerogel prepared in Example 4. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and beneficial effects of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0028] Example 1

[0029] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, and the specific steps are as follows:

[0030] Step 1: Using tetrahydrofuran as an organic reagent, add 1.0 g of octaaminophenyl caged polysilsesquioxane to 5 ml of tetrahydrofuran, and stir until completely dissolved and mixed evenly;

[0031] Step 2: Using phthalic acid as an organic acid, add 2.85 g of terephthalic acid into a mixed solvent consisting of 5 ml of tetrahydrofuran and 1 ml of deionized water, and stir until completely dissolved and mixed evenly;

[0032] Step 3: Add the mixed solution obtained in step 2 dropwise at a rate of 0.4 ml / min into the solution obtained in step 1 under stirring at 70°C. Stop stirring immediately after the addition is completed and let stand to wait for gelation;

[0033] Step 4: After the wet gel obtained in step 3 is aged at 60°C for 96 hours, it is fully solvent-displaced with n-hexane 10 times the volume of the gel, with a single displacement time of 8 hours and a total of 3 displacements;

[0034] Step 5: The wet gel obtained in step 4 is subjected to gradient atmospheric pressure drying operation, with a drying starting temperature of 80°C, a heating rate of 20°C / h, and an end temperature of 140°C. After heating to the end temperature and maintaining it for 2 hours, a high-strength SiO2 aerogel is obtained.

[0035] The SEM image of the high-strength SiO2 aerogel prepared in this example is shown in FIG. Figure 1 As shown, the SiO2 aerogel at 0.20g / cm 3 Based on the structure of low density and high porosity of 89.6%, the compressive strength is 17.5MPa, the fracture deformation is 38.7%, the thermal conductivity is 0.02722W / (m·K), and the static hydrophobic angle is 151.2°.

[0036] Example 2

[0037] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0038] Step 1: The organic reagent is acetone, the amount is 8 ml;

[0039] Step 2: The organic acid is 4,4'-biphenyldicarboxylic acid, the amount used is 2.08 g, and the mixed solvent consists of 8 ml acetone and 4 ml deionized water;

[0040] Step 3: The drop rate is 0.1 ml / min and the temperature is 90°C;

[0041] Step 4: The aging temperature is 80°C and the time is 64h.

[0042] The SEM image of the high-strength SiO2 aerogel prepared in this example is shown in FIG. Figure 2 As shown, the SiO2 aerogel is 0.13g / cm 3 Based on the structure of low density and high porosity of 92.1%, the compressive strength is 5.36MPa, the fracture deformation is 52.4%, the thermal conductivity is 0.03123W / (m·K), and the static hydrophobic angle is 147.3°.

[0043] Example 3

[0044] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0045] Step 1: The organic reagent is ethanol, the amount used is 4 ml;

[0046] Step 2: the organic acid is malonic acid, the amount used is 2.14 g, and the mixed solvent consists of 4 ml of ethanol and 0.8 ml of deionized water;

[0047] Step 3: the dripping rate is 0.2 ml / min and the temperature is 80°C;

[0048] Step 4: Aging temperature is 70°C and time is 72h.

[0049] The SEM image of the high-strength SiO2 aerogel prepared in this example is shown in FIG. Figure 3 As shown, the SiO2 aerogel is 0.24g / cm 3 Based on the structure of low density and high porosity of 86.2%, the compressive strength is 21.4MPa, the fracture deformation is 50.6%, the thermal conductivity is 0.02679W / (m·K), and the static hydrophobic angle is 155.9°.

[0050] Example 4

[0051] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which is different from Embodiment 1 in that:

[0052] Step 1: The organic reagent is chloroform, the amount used is 6 ml;

[0053] Step 2: The organic acid is sebacic acid, the amount used is 3.48 g, and the mixed solvent consists of 6 ml of chloroform and 2 ml of deionized water;

[0054] Step 3: the dripping rate is 0.3 ml / min and the temperature is 90°C;

[0055] Step 4: Aging temperature is 75°C and time is 68h.

[0056] The SEM image of the high-strength SiO2 aerogel prepared in this example is shown in FIG. Figure 4 As shown, the SiO2 aerogel is 0.18g / cm 3 Based on the structure of low density and high porosity of 88.2%, the compressive strength is 15.7MPa, the fracture deformation is 72.7%, the thermal conductivity is 0.02918W / (m·K), and the static hydrophobic angle is 157.7°.

[0057] Example 5

[0058] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0059] Step 1: The organic reagent is acetonitrile, the amount used is 7 ml;

[0060] Step 2: The organic acid is dimethyl terphenyl dicarboxylic acid, the amount used is 6.55 g, and the mixed solvent consists of 7 ml acetonitrile and 3 ml deionized water;

[0061] Step 3: the dripping rate is 0.2 ml / min and the temperature is 80°C;

[0062] Step 4: Aging temperature is 80°C and time is 96h.

[0063] The high-strength SiO2 aerogel prepared in this example has a strength of 0.17 g / cm 3 Based on the structure of low density and high porosity of 86.4%, the compressive strength is 17.3MPa, the fracture deformation is 56.1%, the thermal conductivity is 0.03236W / (m·K), and the static hydrophobic angle is 150.9°.

[0064] Example 6

[0065] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0066] Step 2: the organic acid is 1,3,5-benzenetricarboxylic acid, the amount used is 3.25 g, and the mixed solvent consists of 5 ml of tetrahydrofuran and 2 ml of deionized water;

[0067] Step 3: The drop rate is 0.1 ml / min and the temperature is 90°C;

[0068] Step 4: The aging temperature is 80°C and the time is 72h.

[0069] The high-strength SiO2 aerogel prepared in this example has a strength of 0.19 g / cm 3 Based on the structure of low density and high porosity of 87.1%, the compressive strength is 14.3MPa, the fracture deformation is 40.2%, the thermal conductivity is 0.03004W / (m·K), and the static hydrophobic angle is 153.1°.

[0070] Example 7

[0071] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0072] Step 1: The organic reagent is tetrahydrofuran, the amount used is 4 ml;

[0073] Step 2: the organic acid is dodecanedioic acid, the amount used is 7.51 g, and the mixed solvent consists of 4 ml of tetrahydrofuran and 1 ml of deionized water;

[0074] Step 3: the dripping rate is 0.2 ml / min and the temperature is 80°C;

[0075] The high-strength SiO2 aerogel prepared in this example has a strength of 0.29 g / cm 3 Based on the structure of low density and high porosity of 86.0%, the compressive strength is 26.9MPa, the fracture deformation is 86.7%, the thermal conductivity is 0.03238W / (m·K), and the static hydrophobic angle is 158.6°.

[0076] Example 8

[0077] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0078] Step 1: The organic reagent is ethanol, the amount used is 6 ml;

[0079] Step 2: The organic acid is 2,6-naphthalene dicarboxylic acid, the amount used is 2.61 g, and the mixed solvent consists of 6 ml of ethanol and 2 ml of deionized water;

[0080] Step 3: The drop rate is 0.1 ml / min and the temperature is 75°C;

[0081] Step 4: Aging temperature is 70°C and time is 72h.

[0082] The high-strength SiO2 aerogel prepared in this example has a strength of 0.15 g / cm 3 Based on the structure of low density and high porosity of 90.2%, the compressive strength is 12.1MPa, the fracture deformation is 48.8%, the thermal conductivity is 0.03360W / (m·K), and the static hydrophobic angle is 147.9°.

[0083] Example 9

[0084] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0085] Step 1: The organic reagent is chloroform, the dosage is 5 ml;

[0086] Step 2: The organic acid is azobenzene-4,4-dicarboxylic acid, the amount used is 5.58 g, and the mixed solvent consists of 5 ml of chloroform and 1 ml of deionized water;

[0087] Step 3: the dripping rate is 0.2 ml / min and the temperature is 80°C;

[0088] Step 4: The aging temperature is 80°C and the time is 64h.

[0089] The high-strength SiO2 aerogel prepared in this example has a strength of 0.19 g / cm 3Based on the structure of low density and high porosity of 86.7%, the compressive strength is 16.8MPa, the fracture deformation is 61.3%, the thermal conductivity is 0.02977W / (m·K), and the static hydrophobic angle is 152.0°.

[0090] Example 10

[0091] This embodiment provides a method for preparing a high-strength SiO2 aerogel with adjustable deformation ability, which differs from Embodiment 1 in that:

[0092] Step 1: The organic reagent is tetrahydrofuran, the amount used is 6 ml;

[0093] Step 2: The organic acid is 1,1-cyclopropyldicarboxylic acid, the amount used is 2.23 g, and the mixed solvent consists of 6 ml of tetrahydrofuran and 2 ml of deionized water;

[0094] Step 3: the dripping rate is 0.4 ml / min and the temperature is 70°C;

[0095] Step 4: Aging temperature is 60°C and time is 64h.

[0096] The high-strength SiO2 aerogel prepared in this example has a strength of 0.15 g / cm 3 Based on the structure of low density and high porosity of 89.9%, the compressive strength is 9.7MPa, the fracture deformation is 52.8%, the thermal conductivity is 0.02863W / (m·K), and the static hydrophobic angle is 150.1°.

[0097] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A method for preparing a high-strength SiO2 aerogel with adjustable deformation capacity, characterized in that: The following steps are involved: Step 1: adding a caged polysilsesquioxane to an organic reagent and stirring until completely dissolved; the caged polysilsesquioxane is an octaaminophenyl caged polysilsesquioxane; Step 2: dissolving an organic acid into a mixed solvent of an organic reagent and deionized water, wherein the type and amount of the organic reagent are the same as those in step 1, and the organic acid is a dibasic or polybasic organic acid; Step 3: at a preset reaction temperature, dropwise add the solution obtained in step 2 into the solution obtained in step 1 under continuous stirring, stop stirring when the addition is complete, and let stand to wait for gelation; Step 4: performing aging and solvent replacement operations on the wet gel obtained in step 3; Step 5: The alcohol gel obtained in step 4 is dried at normal pressure using a gradient temperature rise method to obtain a high-strength SiO2 aerogel with adjustable deformation capacity.

2. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: In step 1, the usage ratio of cage-type polyhalf siloxane to organic reagent is 1 g:4-8 ml.

3. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: In step 1, the organic reagent is tetrahydrofuran, acetone, ethanol, chloroform or acetonitrile.

4. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: In step 2, the organic acid is phthalic acid, 4,4'-biphenyldicarboxylic acid, malonic acid, sebacic acid, dimethylterphenyldicarboxylic acid, 1,3,5-benzenetricarboxylic acid, dodecanedioic acid, 2,6-naphthalene dicarboxylic acid, azobenzene-4,4-dicarboxylic acid or 1,1-cyclopropyldicarboxylic acid.

5. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: In step 2, the volume ratio of the organic reagent to deionized water is 1:0.2-0.

5.

6. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: The molar ratio of the caged polysilsesquioxane in step 1 to the organic acid in step 2 is 1:10-24.

7. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: In step 3, the reaction temperature is 70-90° C., and the droplet acceleration rate is 0.1-0.4 ml / min.

8. The method for preparing the high-strength SiO2 aerogel with adjustable deformation capacity according to claim 1, characterized in that: In step 4, the aging temperature is 60-80° C., and the aging time is 64-96 h.

Citation Information

Patent Citations

  • Bridged polysilsesquioxane aerogel and preparation method thereof

    CN102372851A

  • Fast preparation method of silicon dioxide aerogel

    CN107082431A